RPL22 Overexpression Promotes Psoriasis-Like Lesion by Inducing Keratinocytes Abnormal Biological Behavior - Zeng, Jinrong; Zhang, Yue; Zhang, Hanyi; Zhang, Yuezhong; Gao, Lihua; Tong, Xiaoliang; Xie, Yajie; Hu, Qian; Chen, Chunli; Ding, Shu; Lu, Jianyun (Frontiers in Immunology, 2021)
Background: It is well known that keratinocytes of psoriasis have anti-apoptotic properties including the delayed apoptosis process, the accelerated proliferation metabolism and the postponed differentiation process. However, the specific mechanism leading to the abnormal biological behavior of keratinocytes is still unclear. Objectives: To demonstrate the role and mechanism of increased RPL22 expression in skin lesions of psoriatic patients regulating the abnormal biological behavior of keratinocytes. Methods: We collected clinical samples and constructed IMQ mouse and psoriasis cell models to demonstrate the differential expression of RPL22. Then, we investigated the functions and mechanisms of RPL22 in vitro and in vivo. Results: We discovered RPL22 expression increased significantly in the skin lesions of psoriasis patients and IMQ-psoriasis like mouse models. Furthermore, such increased expression is attributed to hyperacetylation of histone H3K27 in the promoter region of RPL22. Interestingly, we demonstrated that overexpression of RPL22 controls cell cycle by increasing cyclinD1 expression and accelerated CD4+T cells recruitment via upregulating CXCL10 expression. Furtherly, we validated RPL22 overexpression accelerated the development of psoriasiform phenotypes in vivo. Conclusions: These findings suggested that RPL22 regulated keratinocytes abnormal biological behavior to contribute to the occurrence and development of psoriasis, which might be a novel potential molecular target for treatment of psoriasis.